STATE AND RIGHT-WING POPULISM: ANALYSIS ON THE KEMENKO POLHUKAM RI PERSUASION APPROACH IN RESPONDING THE WAVE OF â€œ212â€ MOVEMENT - Rizkimawati, Dinda; Kusumawardhana, Indra (Journal of Islamic World and Politics, 2021)
Basuki Tjahaja Purnamaâ€™s blasphemy case reaped various reactions and criticisms. In the â€œAction of Defending Islam 212â€, where Muslims in Indonesia expressed their anger, the masses demanded that religious blasphemers be brought to justice. It caused a series of demonstrations in Indonesia and instability in their domestic security, especially Jakarta as the capital city. This movement was widely known as the wave of right-wing populism in Indonesia. To respond to an extreme right-wing political movement in Indonesian society, the Coordinating Ministry for Political, Legal, and Security made efforts to persuade the community after the movement. This effort was significant in managing the widening of the narrative and reminding those who used the approach anchor base or key people and communities to help spread the message.